High-speed super resolution imaging of live fission yeast cells - Laplante, Caroline (Methods Mol Biol, 2016)
We describe a step-by-step method for high-speed fluorescence photoactivation localization microscopy (FPALM) of live fission yeast cells. The resolution with this method is tenfold better than spinning disk confocal microscopy.